PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV SDN KARANGREJO 02 SEMARANG PADA PEMBELAJARAN PENDIDIKAN PANCASILA - Ratna Kurnia Novianti; Ikha Listarini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is motivated by the results of observations made by researchers. In observation activities, the results showed that students were less able to apply critical thinking in learning activities. Based on this, it became the basis for research conducted to research the influence of Problem Based Learning on the learning outcomes of class IV students at SDN Karangrejo 02 on Pancasila Education learning at SDN Karangrejo 02. This type of research is quantitative with a pre-experimental design with a one group pretest model. -posttest. The research was carried out at SDN Karangrejo 02 Semarang. The diagnostic test results obtained are used to determine student learning outcomes. The research results show that the application of the Problem Based Learning model can be used as a reference for learning activities that train students' critical thinking skills, and can improve student learning outcomes. Based on this research, the suggestion that researchers can convey is that schools can implement learning activities that involve more critical thinking learning, for example by implementing the Problem Based Learning learning model. With learning activities that train critical thinking skills, it is hoped that it can improve students' critical thinking skills in all aspects of life. The author hopes that this research can become one of the teaching innovation options that can be used by teachers and can be developed for teaching by future researchers.